Proceedings of the Forty-First Annual ACM Symposium on Theory of Computing 2009
DOI: 10.1145/1536414.1536471
|View full text |Cite
|
Sign up to set email alerts
|

Efficient discrete-time simulations of continuous-time quantum query algorithms

Abstract: The continuous-time query model is a variant of the discrete query model in which queries can be interleaved with known operations (called "driving operations") continuously in time. We show that any quantum algorithm in this model whose total query time is T can be simulated by a quantum algorithm in the discrete-time query model that makes O(T log T / log log T ) ⊂Õ(T ) queries. This is the first such upper bound that is independent of the driving operations (i.e., it holds even if the norm of the driving Ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 20 publications
(15 reference statements)
1
72
0
Order By: Relevance
“…Given the results of Childs et al [6] and Cleve et al [19], in which quantum walks are shown to traverse a family of 'glued trees' exponentially faster than any possible classical algorithm, relative to a quantum oracle, we decided to look into quantum walks along glued trees in the non-oracular setting. Note that the algorithm presented in [6] employs continuous-time quantum walks, while in [19] it was shown to also be implementable by discrete-time quantum walks.…”
Section: Efficient Quantum Circuit Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the results of Childs et al [6] and Cleve et al [19], in which quantum walks are shown to traverse a family of 'glued trees' exponentially faster than any possible classical algorithm, relative to a quantum oracle, we decided to look into quantum walks along glued trees in the non-oracular setting. Note that the algorithm presented in [6] employs continuous-time quantum walks, while in [19] it was shown to also be implementable by discrete-time quantum walks.…”
Section: Efficient Quantum Circuit Implementationmentioning
confidence: 99%
“…Note that the algorithm presented in [6] employs continuous-time quantum walks, while in [19] it was shown to also be implementable by discrete-time quantum walks. Both require the use of a quantum oracle.…”
Section: Efficient Quantum Circuit Implementationmentioning
confidence: 99%
“…The problem it faces is that the norm of A G can be super-constant, which slows the simulation. Fortunately, a relationship between the discrete-and continuous-time quantum query complexity models, from [14], allows for removing the norm dependency, at a sub-logarithmic cost to the query complexity. By instead reflecting about the eigenvalue-zero subspace of A G , we efficiently remove the dependence on higher-energy portions of A G .…”
Section: Reflection Structure Of the Algorithmmentioning
confidence: 99%
“…The log over log log factor in Eq. (1.2) comes from converting a certain continuous-time query algorithm into a discrete-query algorithm following [14]. This conversion somewhat obscures the algorithm's structure.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, using the equivalence between continuous-and discrete-time query models in Ref. [24] yields a lower bound for the cost O(L/[ log(L/ )]). Our formal proof below, which uses a version of the adversary method in the continuous-time setting, will avoid the logarithmic correction in the cost.…”
Section: Nondegenerate Eigenpathmentioning
confidence: 99%